THE ROLE OF BORROWED WORDS IN THE FORMATION OF BRANDS - Buriyeva, Nargiza (Журнал иностранных языков и лингвистики, 2021)
This article describes the methods and role of borrowing in the formation of the brand chosen by Uzbek manufacturers. The phonetic process, as well as the psycho-semantic and linguistic characteristics of the names are investigated in the article. The author argues that the main features of the choice of a hybrid name make it more expressive, attractive and aesthetic. The process of assimilation of borrowings leads not only to the appearance of derivatives from neologisms formed by models of both ordinary and random word formation, but also to the appearance of semantic neologisms, created on the basis of metaphorical and metonymic transfers.